Elevated 1st trimester serum uric acid - a risk for gestational diabetes mellitus among South-Indians: a prospective observational, longitudinal study - Rao, Chetana N.; Uthraraj, Kannaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Mildest carbohydrate intolerance during pregnancy may increase the risk of maternal and foetal complications. Studies suggest interesting relationships between elevated 1st trimester SUA and development of GDM, but they have not been consistent and as per our literature search we did find only one or two such studies carried out on South-Indian women in whom, the food habits, genetics, environmental factors differ from rest of the world. Methods: 124 pregnant women were studied with an aim to prospectively evaluate relation between 1st trimester SUA levels with development of GDM. Continuous data were analyzed for average/mean, median and standard deviation; and categorical variables using chi-square, independent t-test, Pearson’s correlation coefficient and ANOVA. Results: 36% of the study sample had risk factors for GDM with an incidence of 22.6%. Pearson correlation with 1st trimester SUA concentration of 3.2 mg/dl as a cut-off point for predicting GDM risk was found to be statistically significant. At cut-off levels of 3.98 mg/dl, risk of women developing GDM requiring insulin therapy in addition to diet was statistically significant. Conclusions: Along with other risk factors, elevated 1st trimester SUA levels is an independent risk factor for development of GDM. If diagnosed early and properly monitored, GDM usually doesn’t affect pregnancy outcome in our population.